2021
DOI: 10.1016/j.celrep.2021.108888
|View full text |Cite
|
Sign up to set email alerts
|

Tunable, division-independent control of gene activation timing by a polycomb switch

Abstract: SUMMARY During development, progenitors often differentiate many cell generations after receiving signals. These delays must be robust yet tunable for precise population size control. Polycomb repressive mechanisms, involving histone H3 lysine-27 trimethylation (H3K27me3), restrain the expression of lineage-specifying genes in progenitors and may delay their activation and ensuing differentiation. Here, we elucidate an epigenetic switch controlling the T cell commitment gene Bcl11b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 109 publications
4
27
0
Order By: Relevance
“…The time evolution of these variables is given by the following rules:Pitrue⟶αi(x1,,xN)V(PTPi)Pi+1,Pitrue⟶βi(x1,,xN)VPiPi1,Xitrue⟶γi(x1,,xN)VPiXi+1-8pcand1em1em Xitrue⟶δixiVXi1.Here, gene i switches from an inactive (active) to an active (inactive) epigenetic state with first-order kinetics, with a stochastic time constant of α i ( β i ). Consistent with work from our laboratory and others [30,38], both locus activation and silencing rates depend on x 1 … x N , such that constants for epigenetic switching depend on regulatory input levels, which may either involve transcription factors or chromatin-modifying enzymes [38]. Once in an...…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…The time evolution of these variables is given by the following rules:Pitrue⟶αi(x1,,xN)V(PTPi)Pi+1,Pitrue⟶βi(x1,,xN)VPiPi1,Xitrue⟶γi(x1,,xN)VPiXi+1-8pcand1em1em Xitrue⟶δixiVXi1.Here, gene i switches from an inactive (active) to an active (inactive) epigenetic state with first-order kinetics, with a stochastic time constant of α i ( β i ). Consistent with work from our laboratory and others [30,38], both locus activation and silencing rates depend on x 1 … x N , such that constants for epigenetic switching depend on regulatory input levels, which may either involve transcription factors or chromatin-modifying enzymes [38]. Once in an...…”
Section: Resultssupporting
confidence: 68%
“…Chromatin modifying enzymes, with their broad action and ability to modulate epigenetic switching at multiple gene loci, could globally alter the overall dynamics of epigenetic switching networks, and affect the speed at which temporal schedules set by these networks unfold. Consistently, disruption of chromatin modifying enzymes often results in changes to the speed of developmental transitions [38,7173].
Figure 6Chromatin regulators can scalably expand or contract developmental timetables to modify total organ size.
…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, the Bcl11b locus undergoes dramatic changes in chromatin state and conformation during activation, including changes in nuclear positioning, DNA methylation, histone modifications, and long-range chromatin looping interactions. [59][60][61] To determine whether these epigenetic mechanisms contribute to timing of Bcl11b activation, the locus was studied using the dualcolor biallelic reporter approach described above ( Figure 4A). By separately tracking expression of each Bcl11b allele in single cells using live imaging, it was revealed that each allele turns on independently during T-cell development, with one allele frequently activating multiple days and cell divisions before another.…”
Section: Bcl11bmentioning
confidence: 99%